Using the CIPP Model to Ensure Administration Evaluation of Academic Department - Shindi, Sanaa (International Journal of Psychosocial Rehabilitation, 2020)
The purpose of this study is to evaluate the academic programs at the university level in light of selected quality standards (CIPP) based on a survey. The present study uses the descriptive-analytical approach, whereby the researcher collects data and analyzes them in order to make a judgment about the extent of applying quality standards in the initial studies programs. The aim is to improve these programs to be in line with the quality standards for the academic programs. The study population consists of a sample of 20 academic departments evaluated by interviewing about 65 faculty members: (46) males, and (19) females. In this study, the evaluation questionnaire is adopted from ((Rudebjer, Taylor and Del,2001) & (Taylor 2003) which is based on the CIPP evaluation model (Stufflebeam DL. 1983)